Respuesta :

Answer:

D- (3, 1).

Step-by-step explanation: Add the first equation so you can figure out what x equals. Then, plug the value into your next equation in order to find y. Hope this helps. :)

For this case we have the following system of equations:

[tex]2x + 4y = 10\\3x-4y = 5[/tex]

We solve by the method of elimination, then:

We add both equations:

[tex]2x + 3x = 10 + 5\\5x = 15\\x = \frac {15} {5}\\x = 3[/tex]

We find the value of y:

[tex]3 (3) -4y = 5\\9-4y = 5\\9-5 = 4y\\4 = 4y\\y = \frac {4} {4}\\y = 1[/tex]

Answer:

(3,1)

Option D